Progression of Late-Onset Stargardt Disease - Lambertus, S; Lindner, M; Bax, N; Mauschitz, M; Nadal, J; Schmid, M; Schmitz-Valckenberg, S; Hollander, A; Weber, B; Holz, F; van der Wilt, G; Fleckenstein, M; et al. (Association for Research in Vision and Ophthalmology, 2016)
Purpose: Identification of sensitive biomarkers is essential to determine potential effects of emerging therapeutic trials for Stargardt disease. This study aimed to describe the natural history of late-onset Stargardt, and demonstrates the accuracy of retinal pigment epithelium (RPE) atrophy progression as an outcome measure. Methods: We performed a retrospective cohort study collecting multicenter data from 47 patients (91 eyes) with late-onset Stargardt, defined by clinical phenotype, at least one ABCA4 mutation, and age at disease onset ≥ 45 years. We analyzed RPE atrophy progression on fundus autofluorescence and near-infrared reflectance imaging using semiautomated software and a linear mixed model. We performed sample size calculations to assess the power in a simulated 2-year interventional study and assessed visual endpoints using time-to-event analysis. Results: Over time, progression of RPE atrophy was observed (mean: 0.22 mm/year, 95% confidence interval [CI]: 0.19-0.27). By including only patients with bilateral RPE atrophy in a future trial, 32 patients are needed to reach a power of 83.9% (95% CI: 83.1-84.6), assuming a fixed therapeutic effect size of 30%. We found a median interval between disease onset and visual acuity decline to 20/32, 20/80, and 20/200 of 2.74 (95% CI: 0.54-4.41), 10.15 (95% CI: 6.13-11.38), and 11.38 (95% CI: 6.13-13.34) years, respectively. Conclusions: We show that RPE atrophy represents a robust biomarker to monitor disease progression in future therapeutic trials. In contrast, the variability in terms of the course of visual acuity was high.